Non-destructive methods for estimating leaf area density in mango - Junior, Mario Zortéa Antunes; Ferronato, Alessandro; Ferronato, Susan Dignart; Rodrigues, Katiuscia; Gallon, Márcia Martim Pereira; Gomes, Nídia Martineia Guerra; Stieven, Ana Carla; Júnior, José Holanda Campelo (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to estimate the number of leaves in the branches of mango cultivars canopies and to estimate the leaf area density using, respectively, an allometric relation and a light interception model. The work was carried out with the Alfa, Roxa and Malind cultivars, grown at the experimental farm of the Universidade Federal de Mato Grosso, in the municipality of Santo Antônio do Leverger, MT, Brazil. The equations tested for determining the number of leaves had excellent performance, with confidence indexes ranging from 0,85 to 0,94, and can be used as an alternative for estimating the leaf area of the three cultivars. The light interception model also had good performance in estimating leaf density, with confidence indexes ranging from 0,97 to 0,99 and from 0,68 to 0,95 for the Roxa and Malind mango cultivars respectively.
Keywords: Mangifera indica; Beer-Lambert law; PAR